2012
DOI: 10.1021/nl204259t
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube-Bridged Wires with Sub-10 nm Gaps

Abstract: We report a simple but efficient method to synthesize carbon nanotube-bridged wires (NBWs) with gaps as small as 5 nm. In this method, we have combined a strategy for assembling carbon nanotubes (CNTs) inside anodized aluminum oxide pores and the on-wire lithography technique to fabricate CNT-bridged wires with gap sizes deliberately tailored over the 5-600 nm range. As a proof-of-concept demonstration of the utility of this architecture, we have prepared NBW-based chemical and biosensors which exhibit higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The additional enhancement is attributed to the large local electric fields generated in the nanogap adjacent nanocaps, which enhances the Raman excitation of the detecting molecule. When etching time increases over 60 s, the size of nanogap is larger than 20 nm, the Raman peak intensity gradually becomes weak, which is caused by the fact that the plasmon coupling between the adjacent nanocaps is weakened at larger separation distances [35,36]. These results indicate that in our system the maximum optimized SERS performance can be obtained in bimetal Au:Ag nanocap array with the 3 nm gaps size, and Au and Ag nanoparticles on the surface of PS along with the gaps between adjacent PS beads play the same role in SERS enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…The additional enhancement is attributed to the large local electric fields generated in the nanogap adjacent nanocaps, which enhances the Raman excitation of the detecting molecule. When etching time increases over 60 s, the size of nanogap is larger than 20 nm, the Raman peak intensity gradually becomes weak, which is caused by the fact that the plasmon coupling between the adjacent nanocaps is weakened at larger separation distances [35,36]. These results indicate that in our system the maximum optimized SERS performance can be obtained in bimetal Au:Ag nanocap array with the 3 nm gaps size, and Au and Ag nanoparticles on the surface of PS along with the gaps between adjacent PS beads play the same role in SERS enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…Lee et al [60] reported biosensors based on nanotube-bridged wires (NBWs) that are prepared by electrodeposition and on-wire-lithography (OWL) techniques. The scheme and the SEM image of an NBW are shown in Figure 6a and b respectively.…”
Section: Sensingmentioning
confidence: 99%
“…( b ) SEM image of an NBW [60]. ( c ) Schematic diagram showing the DNA sensing experiment using an NBW-based FET [60].…”
Section: Sensingmentioning
confidence: 99%
See 2 more Smart Citations